Effect of food wastewater on biomass production by a green microalga Scenedesmus obliquus for bioenergy generation. (March 2015) - Ji, Min-Kyu; Yun, Hyun-Shik; Park, Sanghyun; Lee, Hongkyun; Park, Young-Tae; Bae, Sunyoung; Ham, Jungyeob; Choi, Jaeyoung
Highlights: A dual strategy for wastewater reuse and biofuel feedstock production. Food wastewater improved the growth and lipid productivity of S. obliquus . Food wastewater supported the algal autoflocculation. Abstract: Effect of food wastewater (FW) on the biomass, lipid and carbohydrate production by a green microalga Scenedesmus obliquus cultivated in Bold's Basal Medium (BBM) was investigated. Different dilution ratios (0.5–10%) of BBM either with FW or salt solution (NaCl) or sea water (SW) were evaluated. S. obliquus showed the highest growth (0.41 g L −1 ), lipid productivity (13.3 mg L −1 day L −1 ), carbohydrate productivity (14.7 mg L −1 day L −1 ) and nutrient removal (38.9 mg TN L −1 and 12.1 mg TP L −1 ) with 1% FW after 6 days of cultivation. The FW promoted algal autoflocculation due to formation of inorganic precipitates at an alkali pH. Fatty acid methyl ester analysis revealed that the palmitic and oleic acid contents were increased up to 8% with FW. Application of FW improved the growth, lipid/carbohydrate productivity and biomass recovery efficiency of S. obliquus, which can be exploited for cost effective production of microalgae biomass.